Generation of political priority for global surgery: a qualitative policy analysis. Issue 8 (August 2015) - Shawar, Yusra Ribhi; Shiffman, Jeremy; Spiegel, David A
Summary Background Despite the high burden of surgical conditions, the provision of surgical services has been a low global health priority. We examined factors that have shaped priority for global surgical care. Methods We undertook semi-structured interviews by telephone with members of global surgical networks and ministries of health to explore the challenges and opportunities surgeons, anaesthesiologists, and other proponents face in increasing global priority for surgery. We did a literature review and collected information from reports from organisations involved in surgery. We used a policy framework consisting of four categories—actor power, ideas, political contexts, and characteristics of the issue itself—to analyse factors that have shaped global political priority for surgery. We did a thematic analysis on the collected information. Findings Several factors hinder the acquisition of attention and resources for global surgery. With respect to actor power, the global surgery community is fragmented, does not have unifying leadership, and is missing guiding institutions. Regarding ideas, community members disagree on how to address and publicly position the problem. With respect to political contexts, the community has made insufficient efforts to capitalise on political opportunities such as the Millennium Development Goals. Regarding issue characteristics, data on the burden of surgical diseases are limited and public misperceptions surrounding the cost and complexity of surgery are widespread. However, the community has several strengths that portend well for the acquisition of political support. These include the existence of networks deeply committed to the cause, the potential to link with global health priorities, and emerging research on the cost-effectiveness of some procedures. Interpretation To improve global priority for surgery, proponents will need to create an effective governance structure that facilitates achievement of collective goals, generate consensus on solutions, and find an effective public positioning of the issue that attracts political support. Funding None.